Peran Keluarga Dalam Mengatasi Emosi Anak Korban Perceraian Orang Tua Studi Kasus Di Rumah Sokat Kabupaten Maluku Tengah - Novia Nofersa Manakutty (INSTITUTIO : Jurnal Pendidikan Agama Kristen, 2024)
This study explores the role of family in addressing the emotional challenges of children from divorced families, focusing on how family members respond to and manage children's emotions. The research was conducted in Rumah Sokat, Central Maluku, with three children aged 4 to 5, who were observed after experiencing parental divorce. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation to understand the family’s role in supporting emotional well-being. Findings show that family plays a crucial role in shaping children’s emotional development, especially after divorce. Families provide emotional and physical support, helping children manage emotions like anger, sadness, and confusion. The involvement of extended family members, such as grandparents, offers additional emotional stability. The study emphasizes the importance of consistent family engagement, including the broader family network, to ensure the child’s emotional recovery. The research highlights the need for families to create a nurturing environment to help children cope with the emotional impacts of divorce. It also recommends involving community members, such as neighbors and peers, to support the emotional development of children. Increased awareness of family involvement is essential to help children build resilience and healthy emotional coping mechanisms